The tourist a new theory of the leisure class - MacCannell, Dean (University of the California Press, 2013)
This book brings social scientific understandings to bear on tourism in the post-industrial age, during which the middle class has acquired leisure time for international travel. This title examines notions of authenticity, high and low culture, and the construction of social reality around tourism.